Meningkatkan Kemampuan Motorik Halus Anak Usia Dini Melalui Kegiatan Meronce di Taman Kanak-kanak Nusa Indah Kota Payakumbuh - Linda Fithria (Departement of Mathematics Education, 2022)
This study aims to determine how the implementation of meronce activities to improve the fine motor skills of early childhood in Nusa Indah Kindergarten, Kec. Payakumbuh Utara Payakumbuh City in the 2022-2023 school year. The type of research used is Classroom Action Research (CAR) which was conducted in two cycles. The subjects of this study were group B students of Nusa Indah Kindergarten in the academic year 2022-2023 with 4 boys and 5 girls, so there were 10 children. The method used in this research is through the assignment of activities in meronce. The data from the research results obtained were then analyzed in order to draw conclusions. The results of the research that the author did show that the increase in children's fine motor skills through meronce activities in the first cycle reached 30% and after the second cycle there was a significant increase, where the children's fine motor achievement became 90%. The implication of this research is that the application of the assignment method through meronce activities can improve the fine motor skills of children in Nusa Indah Kindergarten, Kec. North Payakumbuh Payakumbuh City.